As inter-relações do trabalho pedagógico e a deficiência intelectual - Scussel, Denise Rodovalho (2018)
This research was developed in the Education Post-Graduation Program from the Universidade Federal de Uberlândia, in the research line State, Politics and Education Management. The Theme of this research encompasses the dynamic of the inter relation of the teachers’s pedagocigal work with students with intellectual deficiency.The study is based on the Historical-Cultural Theory of Vygotsky,we searched for elements to comprehend the relationship from what the teacher thinks and knows about intellectual deficiency and how he or she adresses his or her pedagogical work in classroom.The general aim of the research was to comprehend the implications of the senses of especial education and intellectual deficiency teachers have when organizing the pedagogical work in the basic school. With children whose ages ranges from 7 to 12 years old from a public school named Uberaba/MG, from 2010 to 2017. It is a qualitative research focusing on a described exploratory study with 16 (sixteen) teachers from the public school who deal with children with intellectual deficiency. To collect data, it was used a semi-structured interview, the teachers planning and the book activities from the students with and without deficiency. The research enlightens the concepts of intellectual deficiency, approaches the historicity of the studies about intellectual deficiency in the conceptual, legal and educational aspects, highlights the learning process of the students with intellectual deficiency under the light of Vigotski, discusses how the teacher’s occupation is seen nowadays, how the pedagogical work has been performed by the teacher with student with intellectual deficiency and also brings the analysis of the especial education conceptions and the teachers’ intellectual deficiency relating them with their own pedagogical practice. In the studies accomplished by the teachers, it was identified the deficiency as a problem, even if they make an effort to overcome this conception, in their words, the pedagogical practice lies on programs and traditional methodologies in which the differences are disregarded. The analyses enabled us state the thesis that there is a direct inter relationship between the epistemological and common sense comprehension of the teachers when producing their comprehension of the intellectual deficiency and special education that are strong references to the construction of the work with the intellectual deficiency student affecting directly his or her conditions of school development. Thus, the senses the teachers have about intellectual deficiency results from the common sense, poorly affected by the epistemological meaning, which evolves this thematic.